Interpreting Islam In China: Pilgrimage, Scripture, & Language in the Han Kitab - Min Ke-qin@ Omar Min (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2020)
Since the serendipitous “discovery” of the intellectual treasures of the Sino-Muslim literature following the historic international seminar on Islam and Confucianism, held at University of Malaya on 12-14 March 1995, this literature has increasingly become a salient subject of scholarly inquiry, resulting in the emergence of scores of scholarly books, PhD dissertations, and Masters theses. Textual analysis has emerged as an attractive aspect of these new studies of Sino-Muslim literature. Following the footsteps of Murata’s painstaking analysis and translation of Wang Di-yu’s Qingzhen Daxue (the Great Learning of Pure and Real) in her book titled Chinese Gleams of Sufi Light: Wang Dai-yu’s Great Learning of Pure and Real and Liu Chih’s Displaying the Concealment of the Real Realm, and of Liu Zhi’s Tianfang Xingli (Nature and Principle of Islam) in her book titled The Sage Learning of Liu Zhi: Islamic Thought in Confucian Term, the young scholar Kristian Petersen is now revealing his scholarly talent in the field of textual analysis of Sino-Muslim literature